Values-Based Recruitment and Placement of Arabic Language Teachers: A Qualitative Case Study of Human Resource Management in an Indonesian Islamic Boarding School - Anjeli Arda; Hakmi Wahyudi (Al-Wazan: Journal of Arabic Education, 2026)
Studies on human resource management (HRM) in education have widely examined teacher recruitment, selection, and placement in formal school settings, yet limited attention has been given to how these processes operate in pesantren-based Islamic boarding schools, where religious values, kinship networks, and professional qualifications intersect. This study aims to analyze the recruitment, selection, and placement system of Arabic language teachers in a pesantren-based Madrasah Aliyah and to explain how HRM practices are adapted to the institutional culture of pesantren. Employing a descriptive qualitative case-study approach, data were collected through observation and semi-structured interviews with a purposively selected Arabic language teacher directly involved in the recruitment process. The data were analyzed using Miles and Huberman’s interactive model, including coding, categorization, and thematic interpretation. The findings reveal that recruitment combines internal alumni networks and external candidates through flexible, trust-based mechanisms rather than formal committees. Selection emphasizes administrative screening, interviews, microteaching, Arabic proficiency, and, most importantly, personal character alongside academic competence. Teacher placement is determined according to institutional needs, teaching workload, and staff capacity. The study contributes by proposing a contextual HRM model that integrates strategic human resource management principles with pesantren cultural values, demonstrating how character-based recruitment and alumni trust networks can strengthen teacher management while extending HRM theory within Islamic educational institutions